Effects of estradiol and FSH on maturation of the testis in the hypogonadal (hpg) mouse - Mayhew Terry M; Wiles Roman A; Hastie Graham R; Nwagwu Margaret O; Baines Helen; Ebling Francis JP (BMC, 2008)
Abstract Background The hypogonadal (hpg) mouse is widely used as an animal model with which to investigate the endocrine regulation of spermatogenesis. Chronic treatment of these GnRH-deficient mice with estradiol is known to induce testicular maturation and restore qualitatively normal spermatogenesis. The aim of the current studies was to investigate whether these effects of estradiol are direct effects in the testis, or indirect actions via paradoxical stimulation of FSH secretion from the pituitary gland. Methods Initially, Western blot and immunohistochemistry were used to analyse tissues from hpg mice to identify potential sites of action of estradiol. In the main study, hpg mice were treated for 50 days with either an estradiol implant or daily injections of recombinant human FSH, or a combination of both, to determine whether estradiol would have an additive or synergistic effect with FSH on testis development, as assessed by histological analysis and stereological quantification of Leydig, Sertoli and germ cell proliferation. Results Western blot analysis revealed ERα immunoreactive bands of appropriate molecular weight in extracts of testis and pituitary glands from hpg mice, and immunohistochemical studies confirmed ERα in nuclei of anterior pituitary cells and Leydig and peritubular cells in hpg mice. Histological and morphometric analyses revealed that estradiol treatment alone was as effective as FSH in promoting Sertoli cell production and proliferation of the seminiferous epithelium, resulting in the production of elongating spermatids. Combined estradiol and FSH treatment did not produce a greater effect than either treatment alone, though an increased dose of FSH significantly increased seminiferous tubule volume and testis weight and increase Sertoli cell numbers further within the same time frame. In contrast, estradiol caused substantial increases in the wet weight of the seminal vesicles, whereas FSH was without effect on this tissue, and did not augment the actions of estradiol. Conclusion As ERalpha receptor is abundantly expressed in the pituitary gland of hpg mice, and estradiol did not exert effects on testis development over and above those of FSH, we conclude that the action of estradiol on testis development in hpg mice is predominantly via the stimulation of pituitary FSH release.